Improving drying characteristics and quality attributes of edible bird’s nest (EBN) processed under intermittent IR-UVC assisted drying - Gan, Shu Hui (2017)
The quality of Malaysian edible bird’s nest (EBN) is still regarded inferior due to issues related to nitrite content. In August 2011, the Chinese government imposed a ban on EBN products imported from Malaysia, due to the high level of detectable nitrite (NO2-). This nitrite contamination issue has made a great impact to the edible bird’s industry whereby many EBN farmers, traders and exporters are severely affected. In 2012, the China-Malaysia negotiations agreed on the use of radio frequency identification (RFID) tags on every individual package of Malaysian EBN and set the allowable nitrite limit to be less than 30 ppm, in order to allow exportation of Malaysian EBN to China.